The Effect of Halal Certification and Entrepreneurial Marketing on the Successful Small and Medium-sized Enterprises of Food Products - Hibatul Hasanah; Ma'mun Sarma; Jono Mintarto Munandar (Journal of Economics, Business, and Accountancy Ventura, 2023)
This research aims to examine the effect of halal certification and entrepreneurial marketing on the successful small and medium-sized enterprises (SMEs) of processed food products and investigate the dominant factors affecting the successful business of food products. A quantitative method supported by Structural Equation Modeling Partial Least Square (SEM-PLS) is employed to conduct this research. Seventy-one respondents from SMEs actors of food products registered in the Institute for the Study of Food, Drugs, and Cosmetics of the Indonesian Ulema Council (LPPOM MUI) of Riau Province and had the halal certification became the research sample. They are selected using a purposive sampling technique. This research reveals that halal certification positively affects a successful enterprise, while entrepreneurial marketing, directly and indirectly, positively affect a successful business. In addition, entrepreneurial marketing positively affects halal certification. It interprets that halal certification and entrepreneurial marketing are the significant factors determining the successful enterprise of food products. Furthermore, the dominant factors affecting the successful business of processed food products are the certainty of material quality based on the halal concept and consumer preference (halal certification), the level of ability to weave the relation with government (entrepreneurial marketing), and marketing performance (successful business). So, halal certification and entrepreneurial marketing are the essential factors that have to be considered by entrepreneurs to achieve a successful enterprise of food products.Â Â